Research of current postgraduate nursing training courses in ICU: a systematic review. - Galli, Alessia; Gatti, Chiara; Pelusi, Gilda (Journal of Biomedical Practitioners, 2022)
INTRODUCTION Critical care nurses need the ability to integrate advanced theoretical knowledge and practical skills to meet the needs of critical patient care. OBJECTIVE The study presented in this paper wants to research the postgraduate training courses for critical care nurses the techniques that improve more their knowledge and skills. METHODS The authors conducted a systematic review lasting 7 months on three different databases. A search string was placed, based on the selected PICO. A PRISMA flow chart was drawn up. The inclusion and exclusion criteria were established. Several quality assessment tools were used. Results: the search string yielded 506 articles. After the removal of duplicates, the selection with the inclusion and exclusion criteria and the qualitative evaluation; the review included 41 studies. DISCUSSION AND CONCLUSIONS The survey affirms the importance to continuously update the knowledge and skills of the staff who give assistance in high care complexity situations. A lack of uniformity in the definition of standardized training courses emerged from the study. Australian research has given the possibility to develop a tool to evaluate the expected practice level after a training program. Simulation is identified as the best teaching strategy for postgraduate courses in the critical area.